Analysis of revetment construction stability in Kedungu Beach, Tabanan Bali - Indriasari, Vivi Yovita; Risandi, Johan; Akhwadhy, Rudhi (JURNAL SUMBER DAYA AIR, 2017)
Study in Kedungu Beach which has a wide sand dunes and dense vegetation. This place is usually used for tourism by local residents. Causes of erosion is awave come in the form an angle, create longshore current, and litoral drif sediments. The condition is very alarming, because it erodes the amount of land owned by residents. Until now there is no goverment handling yet, only the efforts of the local community by building sea walls and currently also not in a proper condition. Based on the analysis of the data captured in the field and numerical modeling methods, resulting the methode to overcome the erotion problem, i.e. build coastal protection structures such as revetment, where the structure serves as an incoming wave damper and defend the coastline. The purpose of this paper is to provide an overview of the structure stability of revetment against coastal erosion. Stability analysis takes into account the stability of the rolling, sliding, and soil bearing capacity decrease. The dimension and design ofrevetment is secure from overturning (SF = 7.669 > 2); sliding (SF = 4.082>1,5) and bearing capacity support (17.498>3). From this analysis concluded that in the revetment structure design safe and can be applied in the study area. Analysis of the stability of the revetment structure is expected to reduce the level of damage to the building structure coast and surrounding buildings.